PENGARUH MODEL PEMBELAJARAN GENERATIVE LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI LUAS LINGKARAN - Rina; Hani Handayani; Setiawati, Titi (JESA-Jurnal Edukasi Sebelas April, 2025)
This research is motivated by the low ability to solve mathematical problems in mathematical learning material area of the circle. The solution that is expected to improve mathematical problem solving skills is by using a generative learning model. The method used is an experiment in the form of a one group pretest-posttest research design. The instrument used is a student’s mathematical problem solving ability test sheet before (pretest) and after (posttest) with a total of 5 essay questions. The subjects in this study were students of class VI SDN Paniis, totaling 10 studenst. Based on the calculation of the pretest and posttest data that has been carried out through the t-test of the total number of students as many as 10 people, the average value = 36, standad deviation = 11,624, = 9,793 and = . Thus it shows that - = = 9,793 = with the information that is rejected and is accepted. So that it can be concluded that: There is an influence of generative learning model on students’ mathematical problem solving ability in the material of circle area of class VI SDN Paniis in the academic year 2021/2022.